The Role of Character Education in the Digital Era - Ahmad Ramdani; Asep Mulyana Akbar; Akbar Hidayah; Ikmah Wati (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The era of digitalization has significantly influenced human life. In reality, the negative impacts of digitalization have become a major concern that must be addressed immediately. This phenomenon can be seen in the decline of character and morality among the younger generation in today’s digital era. Character education, as a moral foundation in everyday life, plays an important role in the digital age. This study aims to analyze the role of character education in the digital era, the values applied within character education, and the integration of education with digital technology. The data sources in this study were descriptive data derived from a literature review approach. The findings indicate that character education makes a significant contribution as a moral foundation in the era of digitalization. The values embedded in character education play an essential role in human life in the digital era, while the integration of education with digital technology must be balanced with responsibility and morality in order to minimize the negative impacts of digitalization. This study recommends the need for strong collaboration among the government, educational institutions, educators, the younger generation, and other stakeholders in implementing character education in the digital era.